Women’s media use and preferences of media-based interventions on lifestyle-related risk factors in gynecological and obstetric care: a cross-sectional multi-center study in Germany - Bombana, Manuela; Wittek, Maren; Müller, Gerhard; Heinzel-Gutenbrunner, Monika; Wensing, Michel (International journal of environmental research and public health, 2021)
This study aimed to investigate factors affecting (1) women’s media use regarding health-related behaviors during pregnancy and lactation, (2) women’s preferences for media format, and (3) the content of media-based interventions on lifestyle-related risk factors during pregnancy and lactation. A cross-sectional observational multi-center study of pregnant and lactating women and women of childbearing age was carried out in 14 randomly selected obstetric and gynecologic care settings in the 12 most populated cities in Baden-Wuerttemberg, South-West Germany. Data from 219 surveyed women showed that older women, pregnant women, and lactating women have a higher probability of using media during pregnancy and lactation, respectively. The majority of women preferred a combination of analog and digital media-based interventions in gynecological (46.9%) and obstetric (47.1%) care settings and at home (73.0%). Women would like to see information brochures and flyers on health-related behaviors during pregnancy and lactation for use in gynecological and obstetric care settings, and for media use at home, they would like to have books. The probability of preferring the favored media formats in gynecological and obstetric care settings and at home were associated with pregnancy status, relationship status, socioeconomic status (SES), ethnicity, and health insurance status. About 80% of the surveyed women preferred media content regarding recommendations for a healthy lifestyle and healthy behavior during pregnancy and lactation. All of the independent variables were associated with the probability of preferring a specific media content. The SES was found to play a major role in the probability of preferring a specific media content, followed by pregnancy status, ethnicity, and health insurance status. The results from our study provide a basis for tailored preventive interventions in gynecological and obstetric care settings and for use at home. The results imply that a woman can be reached before conception, during pregnancy, or during lactation with preventive measures tailored to their requirements; however, acceptance may vary across personal attributes, such as SES, ethnicity, and others.
Gesehen am 11.11.2021